MEASURING THE IMPACT OF FINANCIAL SUSTAINABILITY ON THE UNEMPLOYMENT RATE IN IRAQ (2014-2024) (World Economics and Finance Bulletin, 2025)
This study aims to measure the impact of fiscal sustainability on the unemployment rate in Iraq during the period (2014–2024), in light of the economic and political challenges the country faced, particularly after the 2014 oil price crisis and the 2020 COVID-19 pandemic. The study relies on an econometric analysis approach using the Autoregressive Distributed Lag (ARDL) model to measure the relationship between fiscal sustainability indicators (fiscal deficit, public debt-to-GDP ratio, and investment spending) and the unemployment rate. The results showed a direct relationship between a worsening fiscal deficit and rising unemployment, versus an inverse relationship between investment spending and declining unemployment rates